2012
DOI: 10.1186/1471-2458-12-321
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of pre-travel health-seeking practices among travelers departing Sydney and Bangkok airports

Abstract: BackgroundPre-travel health assessments aim to promote risk reduction through preventive measures and safe behavior, including ensuring travelers are up-to-date with their immunizations. However, studies assessing pre-travel health-seeking practices from a variety of medical and non-medical sources and vaccine uptake prior to travel to both developing and developed countries within the Asia-Pacific region are scarce.MethodsCross-sectional surveys were conducted between July and December 2007 to assess pre-trav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
56
3
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 32 publications
5
56
3
5
Order By: Relevance
“…[1] The practice of travel vaccination in this study was found to be very low which was similar to the findings of an Australian and Bangkok study but different from Greek and Nigerian studies where the practice of travel vaccination was found to be high. [1,2,13,14] Reasons of low practice in this study were not required for country of vaccination followed by non-awareness, while in other studies, the reasons were paucity of information on travel vaccination, distressing protocols and requirement for the vaccination, cost of vaccination as well as poor monitoring system for ensuring travel vaccination at the entry and exit points of the countries, unaware of being at risk, low knowledge of vaccination being important for traveling, cost of the vaccination, and side effects. [1,10,14] The knowledge about travel vaccination and malaria prophylaxis was found to be good in this study which was similar to the results of other studies.…”
Section: Discussionmentioning
confidence: 99%
“…[1] The practice of travel vaccination in this study was found to be very low which was similar to the findings of an Australian and Bangkok study but different from Greek and Nigerian studies where the practice of travel vaccination was found to be high. [1,2,13,14] Reasons of low practice in this study were not required for country of vaccination followed by non-awareness, while in other studies, the reasons were paucity of information on travel vaccination, distressing protocols and requirement for the vaccination, cost of vaccination as well as poor monitoring system for ensuring travel vaccination at the entry and exit points of the countries, unaware of being at risk, low knowledge of vaccination being important for traveling, cost of the vaccination, and side effects. [1,10,14] The knowledge about travel vaccination and malaria prophylaxis was found to be good in this study which was similar to the results of other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Seyahat edenler ül-kelerine dönerken buralarda edindikleri patojenleri de taşıyabil-mekte ve bulaşıcı hastalıkların küresel yayılımına neden olabilmektedirler (8,9). Buna en belirgin örneklerden biri 2003 yılında Çin'de başlayıp Kanada, ABD, farklı Avrupa ve Asya ülkelerine yayılan SARS-Coronavirus'un neden olduğu ölümcül solunum yolları enfeksiyonu olan SARS'dır (SARS: Severe Acute Respiratory Syndrome) (7).…”
Section: Introductionunclassified
“…Bulaşıcı hastalıklar yönünden kontrol altında olan bir ülke için seyahat, belki de tek risk faktörüdür (8). Gelişmekte olan ülke-leri ziyaret edenlerin yarısından fazlasının hasta olduğu, %8'inin de medikal desteğe ihtiyaç duyduğu bildirilmiştir (11).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Clinicians and private medical practitioners should be made acquainted with the travel medicine/diseases which may occur in patients with a history of foreign travel so that they should be aware of the risks when treating them. 8 To conclude, in order to avoid any deviation from healthy status, every traveler has to be proactive. Emporiatrics will have an important role in future years not only in identifying new risks but also in establishing new methods of therapy and prophylaxis for the travelers' benefit.…”
mentioning
confidence: 99%